Chemical Modification of Hyaluronan and Their Biomedical Applications - Hintze, Vera; Schnabelrauch, Matthias; Rother, Sandra (Frontiers in Chemistry, 2022)
Hyaluronan, the extracellular matrix glycosaminoglycan, is an important structural component of many tissues playing a critical role in a variety of biological contexts. This makes hyaluronan, which can be biotechnologically produced in large scale, an attractive starting polymer for chemical modifications. This review provides a broad overview of different synthesis strategies used for modulating the biological as well as material properties of this polysaccharide. We discuss current advances and challenges of derivatization reactions targeting the primary and secondary hydroxyl groups, or carboxylic acid groups and the N-acetyl groups after deamidation. In addition, we give examples for approaches using hyaluronan as biomedical polymer matrix and consequences of chemical modifications on the interaction of hyaluronan with cells via receptor-mediated signaling. Collectively, hyaluronan derivatives play a significant role in biomedical research and applications indicating the great promise for future innovative therapies.